Using WGCNA and transcriptome profiling to identify hub genes for salt stress tolerance in germinating soybean seeds - Pan, Lijun; Chen, Yifan; Ren, Zeyu; Khojely, Dalia Mohamedkheir; Wang, Siyu; Li, Yueming; Ibrahim, Seifeldin Elrayah; Fan, Sujie; Song, Yang; Zhang, Zhuo; Wei, Jian (Frontiers in Plant Science, 2025)
Salinized soil can significantly hinder soybean growth, leading to a reduction in overall yield. To address this issue, identifying key genes related to salt tolerance in soybeans is essential for improving their resistance to salinity and ensuring sustainable development of soybean production. While current research predominantly focuses on salt tolerance during the seedling stage, there is still a lack of comprehensive studies on the genes involved in salt tolerance during the germination stage. This study established the optimal screening criteria by phenotyping the salt-tolerant variety R063 and the salt-sensitive variety W82 during the germination stage under salt stress. RNA-seq analysis was performed on 24 samples from both varieties at 36 and 48 hours under two different salt concentrations (0 and 150 mM/L NaCl). Differential expression analysis revealed that the salt-tolerant variety R063 exhibited the fewest differentially expressed genes (DEGs) compared to its control after 48 hours of salt stress. A total of 305 DEGs were commonly identified between the salt-tolerant variety R063 and the salt-sensitive variety W82 under salt stress at both time points. Additionally, 187 DEGs were commonly identified between R063 under salt stress and its corresponding control group across the two time points. Gene ontology (GO) enrichment analysis revealed that the differentially expressed genes were significantly enriched in ADP binding, monooxygenase activity, oxidoreductase activity, defense response, and protein phosphorylation signaling pathways. The weighted gene co-expression network analysis (WGCNA) method was employed to identify modules strongly correlated with salt tolerance during soybean germination. Candidate genes associated with soybean sprouting salt tolerance were identified by evaluating the connectivity and expression profiles of genes within these modules. These findings provide a theoretical foundation for further elucidating the molecular mechanisms underlying salt tolerance during soybean germination and present new genetic resources for studying this trait.